Hambatan Pelaksanaan Program Directly Observed Treatment Short - Course (DOTS) di Negara Berkembang : Sebuah Tinjauan Sistematik - Venia Oktafiani (Jurnal Sains & Kesehatan, 2023)
Tuberculosis is a global burden with most cases occurring in developing countries. After the implementation of Directly Observed Treatment Short-course (DOTS), the incidence of tuberculosis decreased. Despite, studies reported constraints in implementing this program. This study aims to describe the challenges of DOTS implementation in developing countries narratively. Methods a search strategy through PUBMED was used to identify relevant articles. 10 relevant articles were included from 349 records. The studies were conducted in 8 developing countries namely South Africa, Sub-Saharan Africa, Brazil, Ethiopia, Indonesia, Angola and Nigeria. All articles included was extracted and categorized in ten main points regarding the challenges of the implementation of DOTS program. Results: There were 10 main points of challenges in implementing the DOTS strategy in developing countries : lack of access to health centres, managerial and organizational service problems, lack of health education-related tuberculosis, lack of supervision, TB co-infection, lack of trained health workers, smoking, alcohol, and drug abuse during treatment, patient-health professional relationship, lack of food availability and interruption during treatment. The Conclusion is the implementation of the DOTS strategy encounters many challenges in developing countries where lack of health facilities, managerial and organizational service problems and lack of education-related TB are the main challenges to implement the program.